Imposed identities and limited opportunities: Advocacy agency staff perspectives on the construction of their clients with intellectual disabilities - Povee, Kate; Roberts, Lynne; Bishop, B. (2015)
Intellectual disability is commonly conceptualised as stigmatised identity; however, within the literature, the notion of a damaged identity is contested. The aim of this research was to explore the social construction of intellectual disability from the perspective of staff who work closely with people with intellectual disabilities. Informed by a contextualist perspective, this research was based on interviews with five staff members of an advocacy agency in a regional area of Australia. Causal layered analysis was used to deconstruct the interview data. Analysis of the interactions that emerged across the causal layers revealed a complex dynamic of world views, which served to dehumanise people with intellectual disabilities and blame them for their own fate (victim blaming). For transformative change to occur, understandings of the 'problems' of intellectual disability must be reformulated and those social structures and processes that support the relationship between the powerful and the powerless must be challenged.